Tinjauan Analisis Wacana Kritis pada Struktur Teks Anekdot Hasil Siswa Kelas X Berdasarkan Gender di SMKN 2 Kota Bandung Tahun Pembelajaran 2015 – 2016 - Romlah, Siti (Wistara: Jurnal Pendidikan Bahasa dan Sastra, 2020)
The ability of students in making the text structure anecdotes from the point of Critical Discourse Analysis is used as the indicator is a textual dimension that includes cohesion, coherence, grammar and diction. Of the four elements are used as indicators votes captioning anecdotes on students by gender (male and female) can be seen to have capabilities that differences in instructional text anecdotes, the results obtained from the elements of cohesion in the text of anecdotes students generally use the pronouns I and you , because the contents of anecdote is also a dialogue, then it is reasonable person pronouns to one and two are used. Then the word coherence is mentioned and as well as that, the students are already familiar with the conjunctive, while conjunctive other less popular in the eyes of the students, it shows the weakness of students in a variety of making sentences. For terms of grammar seemed once differences in the ability of students men and women, women tend to be scrupulous in making sentences, sentences that made many are forming complex sentences, while boys tend to be careless in making sentences made more simplex. Diction of elements also seen male language more logical than women, as if women visible element of feeling that comes in, it looks at all the different characteristics of students by gender (male and female) in making the text anecdotes. Especially of proficiency.